KEMAMPUAN MENULIS CERITA PENDEK SISWA KELAS XI MADRASAH ALIYAH MUHAMMADIYAH PEKANBARU - Putriwati, Linda; Sinaga, Mangatur; Razak, Abdul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Ability to write a short story students of class XI Madrasah Aliyah Muhammadiyah Pekanbaru aims to find out how the level of ability to write short stories of students of class XI Madrasah Aliyah Muhammadiyah Pekanbaru and know whether or not there is a difference in the ability to write short stories between students of class XI IPA and class XI IPS Madrasah Aliyah Muhammadiyah Pekanbaru. Writing short stories is a person's ability or ability to use his ideas, thoughts, knowledge, and life experiences in clear, expressive, readable and easily understood languages. The method used in this research is quantitative descriptive method. Sources of data used is the score of the ability to write short stories of students of class XI Madrasah Aliyah Muhammadiyah Pekanbaru. Tests conducted using the parametric test, using two different samples of one sample and two different samples of two samples. Based on the results of the test, it can be concluded that the ability to write short stories of students of grade XI Madrasah Aliyah Muhammadiyah Pekanbaru is moderate and there are differences in the ability to write short stories between class XI IPA with class XI IPS Madrasah Aliyah Muhammadiyah Pekanbaru.Keywords: Short stories, writing skill